1998
DOI: 10.1080/001401398186630
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exercise and dehydration on postural stability

Abstract: The aim of this study was to investigate the effects of exercise-induced and thermal dehydration on postural balance. Eight male subjects cycled for 2 h at a power output equal to 57-63% VO2max on two different occasions: once without drinking (NF) and once with intake of 1.9 l of a carbohydrate-electrolyte solution (FR). Before and after the exercise test, the velocity of the centre of pressure (COP) excursion was measured on a force platform during 30-s bipedal standing in normal position, feet side by side,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 11 publications
5
38
1
Order By: Relevance
“…Using varied fatigue protocols, other researchers 8,11,15,16,28 have found similar results, observing postural control deficits after bouts of exercise. Yaggie and Armstrong 29 observed transiently degraded postural control after fatigue from bouts of exercise performed on a cycle ergometer as measured by postural sway.…”
Section: Effect Of Each Exercise Protocol Heart Rate and Rating Of supporting
confidence: 64%
See 2 more Smart Citations
“…Using varied fatigue protocols, other researchers 8,11,15,16,28 have found similar results, observing postural control deficits after bouts of exercise. Yaggie and Armstrong 29 observed transiently degraded postural control after fatigue from bouts of exercise performed on a cycle ergometer as measured by postural sway.…”
Section: Effect Of Each Exercise Protocol Heart Rate and Rating Of supporting
confidence: 64%
“…9 Thus, a postexercise recovery time of 20 minutes has been recommended, so the effect of fatigue does not compromise the sideline postural control assessment. 8,[15][16][17][18] Our findings suggest that athletic trainers and other clinicians who choose to use the BESS as part of their sideline assessment after a suspected mild TBI should wait at least 13 minutes for the effects of fatigue to lessen and the athlete to return to a resting state. The sideline assessment will then be more comparable with baseline, which increases the validity of attributing postural control deficits noted during the sideline assessment to a potential mild TBI.…”
Section: Clinical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that fatigue, which is typically an internal perturbation, may alter this function (Nardone et al 1997;Johnston et al 1998;Vuillerme et al 2001a, b;Derave et al 2001Derave et al , 2002. All these studies found that muscular fatigue caused a temporary destabilising effect, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, muscle fatigue induced by exercises strongly soliciting energy metabolism (e.g. running, cycling, walking, triathlon, ironman triathlon and biathlon shooting) negatively inXuences postural stability and elicits changes in the behavior of motor units and/or central drive characteristics (Lepers et al 1997;Nardone et al 1997Nardone et al , 1998Derave et al 1998Derave et al , 2002Gauchard et al 2002;Nagy et al 2004;Vuillerme and Hintzy 2007). These exhausting physical activities deteriorate sensory proprioceptive and exteroceptive information and/or their integration and/or also decrease the muscular system eYciency (Lepers et al 1997;Nardone et al 1997;Gauchard et al 2002;Nagy et al 2004).…”
Section: Introductionmentioning
confidence: 97%